Magnesiophilic Interface of 3D MoSe2 for Reduced Mg Anode Overpotential - Shen, Tong; Luo, Chengzhao; Hao, Yu; Chen, Yu (Frontiers in Chemistry, 2020)
A large overpotential is often reported for rechargeable magnesium batteries during the deposition/stripping of magnesium, which can be detrimental to the cell performance. In this work, a three-dimensional electrode that mainly composed magnesiophilic MoSe2 (MMSE) has been fabricated and proposed as the substrate for the electrochemical deposition/stripping of magnesium metal. The magnesiophilic interface of MoSe2 has been proven by electrochemical tests of magnesium deposition test. In addition, the electrochemical property of 3D MMSE has been examined by a large-capacity (10 mAh/cm2) magnesium deposition/stripping test. The stable magnesiophilic interface of MMSE has been further confirmed by SEM characterization. Finally, the crucial effect of the magnesiophilic interface of MMSE on the overpotentials have been demonstrated by Mg deposition/stripping test under various current densities.